The poetics of deviance in contemporary American crime fiction - Gregoriou, Christiana (2003)
The study directly explores the three aspects of deviance that contemporary American crime fiction manipulates: linguistic, social, and generic. I conduct case studies into crime series by James Patterson, Michael Connelly and Patricia Cornwell and investigate the way in which the novelists correspondingly challenge linguistic norms, the boundaries of acceptable social behaviour, and the relevant generic conventions. The study particularly explores the nature of the figurative language employed to portray the criminal mind in Patterson, and additionally examines the moral justification of crimes from all three series using the notion of mind style. I also challenge the nature of abnormality as featured in the Connelly series, and argue that crime fiction can be seen as carnival. I name THE MONSTER, THE VAMPIRE, and THE SPOILT CHILD as contemporary criminal archetypes that feature in the genre, and additionally deal with the implications that such a classification bears for the reading of it. In an attempt to re- define the genre, I draw on family resemblance theory, the prototype approach to sense, and defamiliarisation. I argue that novelists such as Paul Auster and Philip Kerr dismember the conventions of crime fiction and defamiliarise the genre. Finally, I hold that the extent to which sub-genres such as Cornwell's forensic series evolve into new genres is a matter of reception. Deviance proves to be a term that means different things for different disciplines, and is difficult to define in the context of anyone. The language used to portray the criminal mind is seen as deviant due to the labelling of criminals as 'socially deviant'. The detectives' social abnormalities are tolerated due to these characters' labelling as ‘socially normal’. Finally, generic deviance goes hand in hand with both other forms of deviance, since character behaviour and mind styles form part of generic conventions. Key words: crime/detective fiction, carnival, Wittgenstein, Bakhtin, deviance/deviation, stylistics, genre, defamiliarisation, James Patterson, Patricia Cornwell, Michael Connelly